Generative Artificial Intelligence in the EFL Writing Context: Students' Literacy in Perspective - Ali Abbas Falah Alzubi (Qubahan Academic Journal)
The birth of generative artificial intelligence (AI) has the potential of developing language learners' English as a foreign language (EFL) writing skills; however, there is a substantial need to ensure that these learners are literate of generative AI-based tools and their potential to enhance learning writing skills. Therefore, the study aims to detect language learners' generative AI literacy in learning EFL writing skills. To achieve this purpose, the descriptive-survey method was used; (278) respondents completed a 30-closed item questionnaire and answered three questions in a semi-structured interview. The results showed that language learners’ generative AI tools literacy in the EFL writing context is at a medium level. Also, the study sample’s responses were not affected by their specialization, but by their GPA and mastery level of using generative AI tools in learning EFL writing skills did impact their responses. The analysis of the interviews revolved around three major themes: Challenges, affordance, and suggestions. In light of the findings, recommendations and suggestions are presented.